Effect of mydriasis on macular and peripapillary metrics in swept-source optical coherence tomography angiography - Zhang, Feng; Li, Ying’an; Du, Zijing; Sun, Hong; Xie, Lijie; Liang, Yingying; Zang, Siwen; Sun, Wei; Yu, Honghua; Hu, Yijun (Frontiers in Endocrinology, 2024)
Introduction: The study aimed to evaluate the effect of mydriasis on macular and peripapillary metrics with swept-source optical coherence tomography angiography (SS-OCTA) in healthy subjects. Methods: Thirty-five healthy subjects were included. The macular region was scanned by the 3×3mm mode and 6×6mm mode, and the peripapillary region was scanned by the 4.5×4.5mm mode on both eyes with SS-OCTA before and after mydriasis. Macular and peripapillary metrics, including retinal vessel density (VD) and fundus thickness were measured by the built-in program. Data of the right eye were analyzed. Results: The signal strength of the scans was comparable before and after mydriasis (all P>0.05). There were no significant differences in foveal avascular zone (FAZ) parameters and retinal VD of most sectors in both macular and peripapillary areas (all P>0.05). Choroidal thickness was decreased, outer and whole retinal thickness was increased in most of the macular sectors after mydriasis (all P<0.05). Choroidal thickness was decreased in all the peripapillary sectors, but whole retinal thickness and GCC thickness were increased in some peripapillary sectors after mydriasis (all P<0.05). Conclusions: FAZ parameters and retinal VD in the most macular and peripapillary regions are not affected by mydriasis. The thickness of the choroid is decreased after mydriasis, while the thickness of retinal layers in some sectors may be increased after mydriasis.